Pertanggungjawaban Pidana Terhadap Anggota TNI Yang Melakukan Tindak Pidana Illegal Logging - Afifuddin Afifuddin; Yuzaili Zulwaqar Rasyid (Jurnal Hukum dan Keadilan "MEDIASI", 2018)
Law Number 18 of 2013 on Prevention and Eradication of Forest Destruction, in Article 82 Paragraph (1) states that "every individual who intentionally cuts down trees in a forest area is illegally sentenced to a minimum of 1 (one) year and maximum of 5 (five) years of sentences and a minimum fine of Rp. 500,000,000 (five hundred million rupiah) and a maximum of Rp. 2,500,000,000 (two billion five hundred million rupiah). Factors causing Illegal Logging committed by members of the Indonesian National Army are economic factors, the need for log is very large and the lack of planning and supervision of the forest. The application of a sanction that is imprisonment for 1 (one) year and a criminal fine of Rp. 500,000,000 (five hundred million rupiah). As for the prevention efforts in the form of preemptive, preventive, and repressive efforts